(untitled) (Comillas Journal of International Relations, 2018)
This article is the communication presented by Teodora Corral during the summer course Crisis of refugees or crisis of European migration policy?, organized in June 2017 by the Chair in Forced Migrants and Refugees of the University Institute of Studies on Migration of the Comillas Pontifical University, the Jesuit Migration Service and the Entreculturas Foundation, at the Menéndez Pelayo University. It is a relevant text for this issue of the Comillas Journal of International Relations, in that it offers a critical reflection, based on first-person knowledge, of the conflict in Central African Republic since 2013, and on its historical and international dimension.